The Legendary Ruler in Medieval Guise: Few Observations on the Iconography of the Belgrade Alexandride - Zivkovic, Milos (Actual Problems of Theory and History of Art, 2025)
The following article is devoted to the miniature paintings of the oldest manuscript of so called Serbian Alexandride, destroyed in 1941. The author focuses attention on some characteristic iconographical details of manuscript illustrations, particularly on peculiar costumes of protagonists, the analogies of which are found in Constantinopolitan courtly costume and in some Serbian medieval wall paintings. One can conclude that some Byzantine manuscript was certainly a prototype for the manuscript, but that conclusion refers only to some of the miniatures. Observation on Western influences on miniatures cannot be maintained. Further arguments can be offered on behalf of earlier hypothesis of creation of manuscript in scriptorium of Archangel monastery near Prizren in the end of the 14th c.
Keywords: Serbian Alexandride; Alexander the Great; manuscripts; miniatures; Byzantine costume